PENGARUH TEKNIK PEMBERIAN AIR CUCIAN BERAS DAN WAKTU PENYEMPROTAN AIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum L.) - Yuli Suwardani; Ansoruddin Ansoruddin; Deddy Wahyudin Purba (Universitas Asahan, 2019)
This research was conducted at the Experimental Garden of the Faculty of Agriculture, Asahan University, Kisaran Timur District, Asahan Regency, North Sumatra Province from March to May 2018. The design used in this study was Factorial Randomized Block Design with two factors and four replications. The first factor is the technique of giving rice washing water with a concentration of 250 ml / liter of water consisting of 2 levels: B1 = watered, B2 = sprayed. The second factor when spraying consists of 3 levels: W1 = morning, W2 = daytime, W3 = afternoon. Parameters observed were plant height (cm), number of fruit per plant (fruit), production per plant (g) and production per plot (kg). The results showed that the technique of giving rice washing water affected plant height up to 72.83 cm, number of fruit per plant 55.38 fruit, production per plant 3.88 kg and production per plot 12.86 kg. Watering time affects plant height at 2 MST, up to 10.85 cm and production per plot 12.49 kg but does not affect the number of fruit per plant and production per plant. The interaction of water-giving techniques and watering time did not affect plant height at all ages, number of fruit per plant, production per plant and production per plot.